The Human Leukocyte Antigen G as an Immune Escape Mechanism and Novel Therapeutic Target in Urological Tumors - Jasinski-Bergner, Simon; Eckstein, Markus; Taubert, Helge; Wach, Sven; Fiebig, Christian; Strick, Reiner; Hartmann, Arndt; Seliger, Barbara (Frontiers in Immunology, 2022)
The non-classical human leukocyte antigen G (HLA-G) is a potent regulatory protein involved in the induction of immunological tolerance. This is based on the binding of membrane-bound as well as soluble HLA-G to inhibitory receptors expressed on various immune effector cells, in particular NK cells and T cells, leading to their attenuated functions. Despite its restricted expression on immune-privileged tissues under physiological conditions, HLA-G expression has been frequently detected in solid and hematopoietic tumor diseases including urological cancers, such as renal cell and urothelial bladder carcinoma. Furthermore, HLA-G has been proposed to play a role in the development and progression of urological cancers. For example, HLA-G expression protects tumor cells from anti-tumor immunity by modulating both the phenotype and function of immune cells leading to immune evasion. This review will discuss the expression, regulation, functional and clinical relevance of HLA-G expression in urological tumors as well as its use as a putative biomarker and/or potential therapeutic target for the treatment of renal cell carcinoma as well as urothelial bladder cancer.